RISK DETECTION IN INDIVIDUAL HEALTH CARE: ANY LIMITS? - Palmboom, Ger (Bioethics, 2010)
Background: Biomedical science is producing an avalanche of data about risk factors, often with a small predictive value, associated with a broad diversity of diseases. Prevention and screening are increasingly moving from public health into the clinic. Therefore, the question of which risk factors to investigate and disclose in the individual patient, becomes ethically increasingly urgent. In line with Wilson and Jungner's public health-related 10 principles for screening, it seems crucial to distinguish important from unimportant health risks. Aim: to explore the ways in which clinicians distinguish important from unimportant health risks. Methods: We interviewed 36 respondents (gastroenterologists and gynaecologists/obstetrics) in 5 focus group interviews and 15 open in-depth interviews on their interpretation of what makes a health risk important. Results: Physicians primarily interpreted importance as the severity of the possible harm, less often its probability. Possibilities of prevention or reassurance strongly influenced their judgment on importance. Discussion: It is not likely that interpreting ‘important’ as ‘severe’ will help in differentiating meaningful from meaningless risk knowledge. A more fundamental change in our ways of dealing with risk may be called for. We discuss existing literature on resilience as an alternative way to deal with risk. Balancing prevention and risk reduction with resilience could be a fruitful direction.